1996
DOI: 10.1071/mu9960089
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Occurrence and Feeding of Birds at Crater Mountain Biological Research Station, Papua New Guinea

Abstract: During 1989-93, 170 species of birds were obnet capture rates. Comparisons among four other sites in served and 1787 individuals captured in mist nets at the southern Papua New Guinea reveal striking similarities Crater Mountain Biological Research Station, Chimbu among sites in number of species and trophic organisation. Province, Papua New Guinea. Populations of many species Range extensions, weights and natural history observations fluctuated on annual or supra-annual schedules; 46 species are reported for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Observations of dwarf cassowaries from 850-1300 m asl in the Haia catchment suggest that the prevailing densities of a hunted population could be less than 1.0 individual/km 2 (Mack, 1995;Mack & Wright, 1996). Southern cassowary densities are known to drop to less than 1.0 individual/km 2 above 20 m asl (Crome & Bentrupperbaumer, 1991).…”
Section: Production Modelmentioning
confidence: 96%
See 2 more Smart Citations
“…Observations of dwarf cassowaries from 850-1300 m asl in the Haia catchment suggest that the prevailing densities of a hunted population could be less than 1.0 individual/km 2 (Mack, 1995;Mack & Wright, 1996). Southern cassowary densities are known to drop to less than 1.0 individual/km 2 above 20 m asl (Crome & Bentrupperbaumer, 1991).…”
Section: Production Modelmentioning
confidence: 96%
“…f Maximum finite rate of natural increase (r max ). g Maximum possible production (Robinson & Redford, 1991) where K is 1.5 individuals/km 2 in Hala and 1.0 individuals/km 2 in Maimafu (Peters, 1983;Crome & Bentrupperbaumer, 1991;Mack, 1995;Mack & Wright, 1996). h For long-lived species with a life span exceeding 10 years (Robinson & Redford, 1991, 1994.…”
Section: Hunter Effortmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has significant implications for cassowary management strategies in Australia, and also in New Guinea, where cassowaries are traditionally harvested for subsistence and trade. In an evaluation of the sustainability of dwarf cassowary Casuarius bennetti capture and trade in Papua New Guinea (Johnson et al 2004), the carrying capacity (K) was calculated from studies of dwarf cassowary abundance (Mack 1995;Mack and Wright 1996), and population densities reported for the southern cassowary (Crome and Bentrupperbäumer 1991). The New Guinea study concluded that live offtake rates of 0.06-0.07/birds km 2 were unsustainable or near unsustainable in the management areas studied.…”
Section: Revised Density Estimates and Cassowary Management In Austramentioning
confidence: 99%
“…Figures from temperate regions are usually lower, with less than half the percentage of cavity nesters as tropical communities [7,61]. The absence of primary excavators, the woodpeckers, from the region suggests that cavities might be more limiting than other forests, and competition for nest sites can be intense [15,62]. But most cavity-using bird species in Neotropical forests use natural cavities rather than woodpecker excavations [63].…”
Section: Importance Of Cavities To the New Guinea Vertebrate Faunamentioning
confidence: 99%